Modelling Chlorine Transport under UnsteadyState Hydraulic Conditions - Aisopou,A; Stoianov,I; Graham,N (ASCE, 2010)
The occurrence of hydraulic transient events in water supply systems may adversely affect the quality of drinking water. Sudden changes in the flow and pressure may cause sediment and biofilm detachment leading to discoloration and loss of residual chlorine. This paper presents the development and evaluation of a 1D model that describes the chlorine transport during steady and unsteadystate (transient) flow conditions. The main objectives for the model development are accuracy, robustness and computational efficiency as it is intended to be used for operational management. The model was developed by coupling the mass transport equation with a comprehensive hydraulic transient solver which accounts for changes in flow, compressibility and inertia effects. The main contribution has been the inclusion of the unsteady shear stress during transient flow conditions with modelling the chlorine transport. This approach differs from existing 1D water quality models which use steady state formulas and which fail to explain sudden changes in residual chlorine. In the model, the unsteady shear stress is determined and its significance to chlorine propagation is evaluated. The value of the unsteady shear stress is used to evaluate the fluctuations of the velocity profile, which are neglected in 1D transport modelling. The effect of the transient velocity profile on chlorine decay is taken into account by using a chlorine decay coefficient which varies for steady and unsteadystate (transient) flows. The validity of the modeling approach is evaluated by benchmarking its performance with a 2D transient model which explicitly considers the 2D velocity profile.